Formulasi dan Evaluasi Sediaan Facemist Kombinasi Ekstrak Etanol Daun Kelor (Moringa Oliefera L) dan Ekstrak Etanol Daun Sirih Cina (Peperomia Pellucida) sebagai Antioksidan - Putri, Okkyana Kusuma; Rohannah, Rohannah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Antioxidants are compounds that can capture free radicals. Free radicals are tissue damage that causes premature aging. Ethanol extract of moringa leaves and ethanol extract of Chinese betel leaves have properties as natural antioxidants and are developed in the form of cosmetics in the form of facemist. This study aims to formulate a combination of ethanol extract of moringa leaves and ethanol extract of Chinese betel leaves from maceration results as a facemist preparation with concentration variations of 0.1%, 0.2% and 0.3%. The three concentrations of the preparation were evaluated including organoleptic tests, homogeneity tests, pH tests, drying time tests and physical stability tests, and antioxidant activity tests were carried out using the DPPH method. Based on the evaluation results, the combination of moringa leaf extract and Chinese betel leaf extract has good physical stability of the facemist. Antioxidant activity at concentrations of 0.1%, 0.2% and 0.3% has an IC50 value of 211.71 (moderate), 146.95 (moderate) and 97.96 (strong) ppm. It can be concluded that the best preparation is at a concentration of 0.3% with an IC50 value of 97.96 ppm which has strong antioxidant activity.